Epidemiology of eating disorders in primary care in children and young people: a Clinical Practice Research Datalink study in England. Issue 8 (4th August 2019) - Wood, Sophie; Marchant, Amanda; Allsopp, Mark; Wilkinson, Kathleen; Bethel, Jackie; Jones, Hywel; John, Ann
Abstract : Objectives: Examination of current temporal trends and clinical management patterns of eating disorders (ED) in primary care is lacking. We aimed to calculate annual incidence rates of EDs in primary care by age, sex and deprivation. We also explored the care received through referrals, psychotropic prescriptions and associated secondary care service use. Participants and settings: A retrospective electronic cohort study was conducted using the Clinical Practice Research Datalink in those aged 11–24 years between 2004 and 2014 in England (n=1 135 038). Results: A total of 4775 individuals with a first ever recorded ED diagnosis were identified. The crude incidence rate was 100.1 per 100 000 person years at risk (95% CI 97.2 to 102.9). Incidence rates were highest in females (189.3 per 100 000 person years, 95% CI 183.7 to 195.0, n=4336), 16–20 years of age (141.0 per 100 000 person years, 95% CI 135.4 to 146.9, n=2348) and individuals from the least deprived areas (115.8 per 100 000 person years (95% CI 109.3 to 122.5, n=1203). Incidence rates decreased across the study period (incidence rate ratio (IRR) 0.6, 95% CI 0.5 to 0.8), particularly for individuals with bulimia nervosa (IRR 0.5, 95% CI 0.3 to 0.7) and from the most deprived areas (IRR 0.5, 95% CI 0.4 to 0.7). A total of 17.4% (95% CI 16.3 to 18.5, n=831) of first ever recorded ED cases were referred from primary to secondary care. 27.1% (95% CI 25.9 to 28.4, n=1294) of individuals had an inpatient admission 6 months before or 12 months after an incident ED diagnosis and 53.4% (95% CI 52.0 to 54.9, n=2550) had an outpatient attendance. Antidepressants were the most commonly prescribed psychotropic medication. Conclusions: New ED presentations in primary care are reducing. Understanding the cause of this decrease (coding behaviours, changes in help-seeking or a genuine reduction in new cases) is important to plan services, allocate resources and deliver effective care.